The Symbolic Landscape of the Berber Cemetery - Hatt, D. G. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1992)
The village cemeteries of the Berber-speaking inhabitants of the High Atlas mountains of Morocco are overgrown with untended masses of végétation which are allowed to disturb, and indeed, eventually, to obliterate, the graves. The resulting landscapes are not, however, simply areas “abandoned to nature” because, in a heavily overgrazed environment like the High-Atlas, such an overgrowth of vegetation requires the systematic exclusion of goats and sheep and the prohibition of wood-gathering, and hence is the resuit of human choice and deliberated action. In other words, what appears to be a “naturel” landscape is in fact an artifice, a “made” landscape, and, as such, is capable of being deciphered. The paper explores various dimensions of this “symbolic landscape” by situating it within the everyday habits and practices of village life.